2019
DOI: 10.1177/1178221819836726
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Feasibility of Brief Compassion Focused Therapy in Individuals in Treatment for Opioid Use Disorder

Abstract: Opioid use disorder (OUD) is reaching epidemic proportions worldwide, and is notoriously difficult to treat. Compassion focused therapy (CFT) has emerged as therapeutic tool for treating individuals exhibiting high levels of self-criticism and low self-esteem, both of which are common in OUD. Until now, however, there had been no research investigating this therapy in patients with OUD. Before running a premature clinical trial, it is important to fully assess the feasibility and acceptability of this treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Although there are studies showing promising efficacy results of ACT in less than four sessions, the average of number of sessions of ACT for CI is approximately six sessions (see Graham et al, 2016). Similarly, although brief CFT interventions seem to be feasible and promising (e.g., Carlyle et al, 2019; Cheli et al, 2020), the average number of sessions of CFT is approximately 10 sessions (see Craig et al, 2020). Future studies should explore differences in efficacy between different lengths and/or intensities of both ACT and CFT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there are studies showing promising efficacy results of ACT in less than four sessions, the average of number of sessions of ACT for CI is approximately six sessions (see Graham et al, 2016). Similarly, although brief CFT interventions seem to be feasible and promising (e.g., Carlyle et al, 2019; Cheli et al, 2020), the average number of sessions of CFT is approximately 10 sessions (see Craig et al, 2020). Future studies should explore differences in efficacy between different lengths and/or intensities of both ACT and CFT.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, while there is mounting literature on the effects of brief ACT interventions (see Dindo et al, 2017), brief interventions have just recently been explored in CFT. Although results suggest that three to four sessions of CFT are feasible (Carlyle et al, 2019), the few studies that explored its efficacy have not used a control condition (Cheli et al, 2020) or have studied the effects in a short follow‐up period (2 months) (Halamová et al, 2020). Post hoc comparisons suggested that both conditions seemed to be effective in reducing illness‐related shame and uncompassionate self‐responding and in increasing valued action, but seemingly at different paces: while illness‐related shame seemed to decrease only from post‐intervention to follow‐ups in ACT, it seemed to decreased from pre‐ to post‐interventions and was sustained at follow‐ups in CFT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CFT also appears to be effective in improving psychopathological symptoms transdiagnostically, potentially through reductions in self-criticism and fears of self-compassion (Cuppage, Baird, Gibson, Booth, & Hevey, 2018). More recent studies also point to promising applications for CFT in treating opioid abuse (Carlyle et al, 2019) and addressing mood symptoms in individuals with dementia (Craig, Hiskey, Royan, Poz, & Spector, 2018). In terms of self-compassion, a recent meta-analysis showed that high levels of self-compassion correlated strongly with low levels of psychopathology (MacBeth & Gumley, 2012).…”
Section: Compassionmentioning
confidence: 99%